Clinical Review of Obstructive Primary Cardiac Tumors in Childhood. (21st August 2013) - Nield, Lynne E.; Mendelson, Michael; Ahmad, Nauman; Manlhiot, Cedric; Jaeggi, Edgar T.; McCrindle, Brian W.
Abstract Objectives This study aims to examine the long‐term outcomes of conservative management compared with surgical resection for obstructive and nonobstructive primary cardiac tumors in children. Design A 20‐year retrospective review of primary cardiac tumors seen in the right ventricular outflow tract (RVOT) and left ventricular outflow tract (LVOT) in children at The Hospital for Sick Children, Toronto, Canada. Student's t‐tests and Fisher's exact chi‐square were used to compare outcomes between the conservatively managed vs. surgical resection groups and the obstructive vs. nonobstructive tumor groups. Results Between 1990 and 2010, we identified 130 children with intracardiac tumors among 52 937 (2.5 per 1000 children, 95th confidence interval: 2.1–2.9 per 1000). Thirty‐six children (28%) had at least one cardiac tumor in the RVOT (n = 13) or LVOT (n = 23). Of those, 14 children had peak outflow gradients of >20 mm Hg at the diagnostic echocardiogram (median age at diagnosis: 4 days, range 0 days–6 months; mean follow‐up: 7.8 ± 4.5 years). Rhabdomyoma was the most common tumor 27/36 (75%). Twelve (33%) patients underwent surgical repair vs. 24 patients who were observed only. There was no difference in survival. Patients who had surgery tended to be sicker (intubated at diagnosis 4/12, 33% vs. 1/23, 4%, P = .04). There were no deaths in either group. One child required reoperation for severe aortic insufficiency, and only one child in the observation group had residual obstruction at most recent follow‐up. Conclusions Primary cardiac tumors in childhood obstructing the RVOT or LVOT are uncommon findings after birth and may be managed nonsurgically in most cases.